Pengaruh Sosial Budaya Masyarakat Terhadap Perkembangan Olahraga Sepaktakraw Kabupaten Kutai Kartanegara - Hasnur, Hasnur; Nasuka, Nasuka; Hadi, Hadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of the research is to analyze the process of community participation related to the development of the Sepaktakraw sport in Kutai Kartanegara Regency, to analyze the socialization process and social interaction of the community regarding development. sports in Kutai Kartanegara Regency. The method in this research uses qualitative and phenomenology to study natural events. The objects in this research were nine sub-districts and in one sub-district one to two villages were taken that had Sepaktakraw sports activities. Documentation, interviews and observation are the methods used to collect data. Research results: Participation from 10 villages, 7 villages were in active condition and 3 villages were in inactive condition, the aim of community participation was in 8 villages whose aim was for entertainment and fitness and only 2 villages whose aim of participation was for achievement; The socialization process from PSTI KUKAR has not gone well because of the lack of support and the program has not been realized so that the social interaction of PSTI Kukar administrators and the community is also not going well. in the form of making matches and training, the socialization process from the community (Club) made matches from 10 villages, 4 villages have made match events. Conclusion, The community participation process has gone well because of the busy competition events and the participation of the village community.. The socialization process from the village/sub-district program is not optimal enough so that community social interaction has not gone well. There is a need for cooperation between policy makers such as PSTI Kukar administrators and the community so that participation, socialization and social interaction can run well. Keywords: Kutai Kartanegara, Sepaktakraw, Social Culture, Society. Kutai Kartanegara